IMPLEMENTATION OF BOOKING INVENTORY AND REPORTING REGIONAL OWNED GOODS - Yosua Nicolas Kandey; Jenny Morasa; Olivia Y M Sardjono (Jurnal Bisnis, Ekonomi, dan Sains, 2024)
Regional property administration is one of the scopes of regional property management, where bookkeeping, inventory, and reporting are a series of activities in the administration of regional property in accordance with the provisions of laws and regulations. Administration of regional property in order to create administrative orders, including compiling reports on regional property that will be used as material for preparing balance sheets of government agencies that provide data so that the implementation of regional property management can be carried out effectively. This study aims to determine the application of opening, inventory and reporting of regional property based on Minister of Home Affairs Regulation No. 47 of 2021 at the Office of the Regional Housing, Settlement and Land Office of North Sulawesi Province. The method used in this study is qualitative descriptive. The results showed that the application of bookkeeping, inventory and reporting of regional property at the office of the Housing, Settlement and Land Office of North Sulawesi Province was in accordance with the Minister of Home Affairs Regulation Number.47 Year 2021 concerning Procedures for Implementing Bookkeeping, Inventory and Reporting of Regional Property.